Biomaterials constructed for MSC-derived extracellular vesicle loading and delivery—a promising method for tissue regeneration - Lu, Yu; Yang, Yu; Liu, Shiyu; Ge, Shaohua (Frontiers in Cell and Developmental Biology, 2022)
Mesenchymal stem cells (MSCs) have become the preferred seed cells for tissue regeneration. Nevertheless, due to their immunogenicity and tumorigenicity, MSC transplantation remains questionable. Extracellular vesicles (EVs) derived from MSCs are becoming a promising substitute for MSCs. As a route of the MSC paracrine, EVs have a nano-sized and bilayer lipid-enclosed structure, which can guarantee the integrity of their cargoes, but EVs cannot obtain full function in vivo because of the rapid biodegradation and clearance by phagocytosis. To improve the efficacy and targeting of EVs, methods have been proposed and put into practice, especially engineered vesicles and EV-controlled release systems. In particular, EVs can be cell or tissue targeting because they have cell-specific ligands on their surfaces, but their targeting ability may be eliminated by the biodegradation of the phagocytic system during circulation. Novel application strategies have been proposed beyond direct injecting. EV carriers such as biodegradable hydrogels and other loading systems have been applied in tissue regeneration, and EV engineering is also a brand-new method for higher efficacy. In this review, we distinctively summarize EV engineering and loading system construction methods, emphasizing targeting modification methods and controlled release systems for EVs, which few literature reviews have involved.